2020
DOI: 10.1007/s40430-020-02649-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ranque–Hilsch vortex tube performances via Taguchi method

Abstract: In this study, by considering the changes in inlet pressures, connection nozzle materials and the number of orifices, the performances of Ranque-Hilsch vortex tubes (RHVTs) were modelled by multiple linear regression method at which carbon dioxide (CO 2) was used as compressed fluid, and optimum operating conditions were tried to be determined by Taguchi method. In the experiment, counterflow RHVTs having Ø10 mm inner diameter and 100 mm body length were used, hot fluid outlet of which was left completely open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The final experimental results found that the optimal cold and hot airflow separation of the swirl flow pipe occurred when the number of nozzles was six, and the material was aluminum. Similarly, Gacke [13] investigated the performance of swirl flow pipes using a linear regression modeling method with a body size of 110 mm and an inner diameter of 10 mm, using compressed CO 2 as the working fluid, 4 and 6 inlet nozzles, and brass and polyamide materials. The optimal operating conditions of the swirl flow pipe were investigated by varying the inlet pressure and comparing the effects of inlet pressure, number of nozzles, and nozzle material.…”
Section: Introductionmentioning
confidence: 99%
“…The final experimental results found that the optimal cold and hot airflow separation of the swirl flow pipe occurred when the number of nozzles was six, and the material was aluminum. Similarly, Gacke [13] investigated the performance of swirl flow pipes using a linear regression modeling method with a body size of 110 mm and an inner diameter of 10 mm, using compressed CO 2 as the working fluid, 4 and 6 inlet nozzles, and brass and polyamide materials. The optimal operating conditions of the swirl flow pipe were investigated by varying the inlet pressure and comparing the effects of inlet pressure, number of nozzles, and nozzle material.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and computational fluid dynamics (CFD) analysis were compared to study the vortex tube using different Reynolds-averaged Navier-Stokes (RANS) models [11]. Unsteady heat and mass transfer processes in a Ranque-Hilsch vortex tube were analyzed to determine tube optimization criteria [12]. Predictive models for the design of counterflow vortex tubes working with perfect gas were reviewed [1].…”
mentioning
confidence: 99%